1993
DOI: 10.1128/jb.175.10.2988-2993.1993
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of lipids A of several Salmonella and Escherichia strains by 252Cf plasma desorption mass spectrometry

Abstract: Plasma desorption mass spectrometry has recently been used with success to characterize underivatized lipid A preparations: the major molecular species present give signals indicating their masses, from which probable compositions could be inferred by using the overall composition determined by chemical analyses. In the present study, plasma desorption mass spectrometry was used to compare structures in lipid A preparations isolated from several smooth and rough strains of Escherichia and Salmonella species. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 26 publications
(35 reference statements)
2
42
0
Order By: Relevance
“…3 . Figure 3A shows the spectrum obtained for E. coli lipid A (24) under the new conditions with the classical hexa-acylated molecular species at m/z 1,797 followed by penta-and tetra-acylated molecular species at m/z 1,570 and 1,361, respectively. For B. pertussis lipid A (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 . Figure 3A shows the spectrum obtained for E. coli lipid A (24) under the new conditions with the classical hexa-acylated molecular species at m/z 1,797 followed by penta-and tetra-acylated molecular species at m/z 1,570 and 1,361, respectively. For B. pertussis lipid A (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Different rough-type bacteria of known lipid A structure were tested: B. pertussis (22), H. influenzae (23), and E. coli (24). MALDI spectra in the negative-ion mode demonstrated that no structural elements were lost upon hydrolysis.…”
Section: Resultsmentioning
confidence: 99%
“…Our assay is based on the observation that the Kdo-lipid A linkage (Fig. 2) is cleaved selectively by pH 4.5 hydrolysis at 100°C in the presence of SDS without measurable loss of ester-linked fatty acids or of the anomeric phosphate (34)(35)(36). The hydrolysis procedure can be applied directly to radioactive cells or to isolated membrane fractions from a sucrose gradient without first extracting LPS with phenol-containing solvents.…”
Section: Discussionmentioning
confidence: 99%
“…The purification steps involved the extraction of phospholipids with chloroform/methanol (1:2) followed by treatment with DNase, RNase and then protease until thin-layer chromatography and ultraviolet spectra showed no detectable contaminants 39 . We check the electrophoretic behavior and mass of all purified samples by SDS-PAGE and mass spectrometry, respectively 40 . Purified LPS from S. typhimurium LT2 was used directly, whereas E. coli 0111B4 and B. pertussis LPS were treated by a procedure that improves LPS solubility by removing divalent cations that form links between molecules 41 .…”
Section: Methodsmentioning
confidence: 99%